BRIDGING DIGITAL INNOVATION AND MATHEMATICS TEACHING: OPPORTUNITIES AND BARRIERS OF USING GOOGLE SITES - Atika Zulfa Rahmani; Fitria Khasanah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Global stagnation of students' mathematics learning outcomes and limited interactivity in conventional learning have given rise to the need for web-based digital innovation. Google Sites has emerged as a potential solution, but a comprehensive study of its form, advantages and disadvantages, and challenges and solutions to its use is still limited. Therefore, this study is important to bridge the knowledge gap in the integration of mathematics education technology. This study aims to systematically identify patterns of Google Sites use in mathematics learning, examine its advantages and obstacles, and offer implementative solutions. This study uses a narrative review approach to empirical literature from 2015–2025 from the Scopus and Sinta databases. Articles were selected based on explicit inclusion criteria, data validity, and contextual relevance; the analysis was conducted thematically to identify patterns and trends. A total of 10 articles were analyzed, resulting in five main themes: LMS functions, ease of access, learning motivation, technical limitations, and solution strategies such as additional media integration and self-directed learning reinforcement. The results show that the effectiveness of Google Sites is greatly influenced by infrastructure readiness and pedagogical design. This study enriches the literature by integrating findings into a practical and theoretical framework. Further research is recommended to evaluate the long-term impact and compare other digital platforms. ABSTRAK Stagnasi hasil belajar matematika siswa secara global serta keterbatasan interaktivitas dalam pembelajaran konvensional memunculkan kebutuhan akan inovasi digital berbasis web. Google Sites muncul sebagai solusi potensial, namun kajian menyeluruh terhadap bentuk, kelebihan-kekurangan, serta tantangan dan solusi penggunaannya masih terbatas. Oleh karena itu, kajian ini penting untuk menjembatani kesenjangan pengetahuan dalam integrasi teknologi pendidikan matematika. Penelitian ini bertujuan mengidentifikasi secara sistematis pola penggunaan Google Sites dalam pembelajaran matematika, menelaah keunggulan dan hambatannya, serta menawarkan solusi implementatif. Studi ini menggunakan pendekatan narrative review terhadap literatur empiris tahun 2015–2025 dari database Scopus dan Sinta. Artikel diseleksi berdasarkan kriteria inklusi eksplisit, validitas data, dan relevansi konteks; analisis dilakukan secara tematik untuk mengidentifikasi pola dan tren. Sebanyak 10 artikel dianalisis, menghasilkan lima tema utama: fungsi LMS, kemudahan akses, motivasi belajar, keterbatasan teknis, dan strategi solusi seperti integrasi media tambahan dan penguatan pembelajaran mandiri. Hasil menunjukkan bahwa efektivitas Google Sites sangat dipengaruhi oleh kesiapan infrastruktur dan desain pedagogis. Kajian ini memperkaya literatur dengan menyatukan temuan dalam kerangka praktis dan teoretis. Penelitian lanjutan direkomendasikan untuk mengevaluasi dampak jangka panjang serta membandingkan platform digital lainnya.